Hepatitis B core-related antigen levels are associated with response to entecavir and peginterferon add-on therapy in hepatitis B e antigen–positive chronic hepatitis B patients. (June 2016) - van Campenhout, M.J.H.; Brouwer, W.P.; van Oord, G.W.; Xie, Q.; Zhang, Q.; Zhang, N.; Guo, S.; Tabak, F.; Streinu-Cercel, A.; Wang, J.; Pas, S.D.; Sonneveld, M.J.; et al.
Abstract: Hepatitis B core-related antigen (HBcrAg), a new serum marker, may be useful in monitoring chronic hepatitis B infection. HBcrAg was measured in 175 hepatitis B e antigen–positive patients treated with entecavir (ETV) with or without peginterferon (PEG-IFN) add-on therapy. Decline in HBcrAg was stronger in patients with vs. without combined response (ETV: −3.22 vs. −1.71 log U/mL, p <0.001; PEG-IFN add-on: −3.16 vs. −1.83 IU/mL, p <0.001) and in patients with vs. without hepatitis B surface antigen (HBsAg) response (ETV: −2.60 vs. −1.74 log U/mL, p <0.001; PEG-IFN add-on: −2.38 vs. −2.15 log U/mL, p = 0.31). HBcrAg was associated with combined response (adjusted odds ratio 0.3, 95% confidence interval 0.2–0.5, p <0.001), but was not superior to quantitative HBsAg (qHBsAg).